Similar healthy osteoclast and osteoblast activity on nanocrystalline hydroxyapatite and nanoparticles of tri-calcium phosphate compared to natural bone - MacMillan AK (Dove Medical Press, 2014)
Adam K MacMillan,1 Francis V Lamberti,1 Julia N Moulton,2 Benjamin M Geilich,2 Thomas J Webster2,3 1RTI Surgical, Alachua, FL, USA; 2Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 3Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: While there have been numerous studies to determine osteoblast (bone forming cell) functions on nanocrystalline compared to micron crystalline ceramics, there have been few studies which have examined osteoclast activity (including tartrate-resistant acid phosphatase, formation of resorption pits, size of resorption pits, and receptor activator of nuclear factor κB [RANK]). This is despite the fact that osteoclasts are an important part of maintaining healthy bone since they resorb bone during the bone remodeling process. Moreover, while it is now well documented that bone formation is enhanced on nanoceramics compared to micron ceramics, some have pondered whether osteoblast functions (such as osteoprotegerin and RANK ligand [RANKL]) are normal (ie, non-diseased) on such materials compared to natural bone. For these reasons, the objective of the present in vitro study was to determine various functions of osteoclasts and osteoblasts on nanocrystalline and micron crystalline hydroxyapatite as well as tri-calcium phosphate materials and compare such results to cortical and cancellous bone. Results showed for the first time similar osteoclast activity (including tartrate-resistant acid phosphatase, formation of resorption pits, size of resorption pits, and RANK) and osteoblast activity (osteoprotegerin and RANKL) on nanocrystalline hydroxyapatite compared to natural bone, whereas osteoclast and osteoblast functions on micron crystalline versions of these ceramics were much different than natural bone. In this manner, this study provides additional evidence that nanocrystalline calcium phosphates can serve as suitable synthetic analogs to natural bone to improve numerous orthopedic applications. It also provides the first data of healthy osteoclast and osteoblast functions on nanocrystalline calcium phosphates compared to natural bone. Keywords: hydroxyapatite, osteoclasts, tri-calcium phosphate, nanocrystalline, nanophase, orthopedics